Improving Thermostability of Chimeric Enzymes Generated by Domain Shuffling Between Two Different Original Glucoamylases - Chen, Zhongxiu; Wang, Longbin; Shen, Yuyu; Hu, Dunji; Zhou, Liying; Lu, Fuping; Li, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
In order to improve enzymatic properties of glucoamylase, six recombinant genes GA1-GA6 were created by domain shuffling of glucoamylase genes GAA1 from Aspergillus niger Ld418AI and GATE from Talaromyces emersonii Ld418TE using overlap extension PCR, and were expressed in Saccharomyces cerevisiae W303-1B, only activities of GA1and GA2 in fermentation broth were higher than that of GAA1 but less than that of GATE. Further research results of GA1 and GA2 indicated that chimeric glucoamylase GA1 and GA2 revealed increased thermostability compared with GAA1 and GATE, although with a slight change in activity and optimal temperature. However, GA1 had almost the same catalytic efficiency as GATE, catalytic efficiency of GA2 was slightly less than that of GATE, but still higher than that of GAA1. The structural analysis showed that the change of enzymatic properties could be caused by the increased and extended α-helix and β-sheet which change the secondary structure and tertiary structure of chimeric glucoamylases. This demonstrated that domain shuffling was feasible to generate chimeric enzyme with novel properties.